Avicenna and cancer study - Rahim, NS; Othman, R. Y.; Shah, MUM; Salleh, HM; Afandi, NHMNA; Sazalli, NAH; Ab Ghani, N; Abas, N; Manap, S.; Suria, MM; Tan, NAS (2M World Sdn Bhd, 2023)
Cancer is the main cause of mortality after COVID-19, reaching pandemicity and remains one of major public health concern. It is worthwhile to consider the perspectives of the renowned medical scholar, Avicenna and he is widely regarded as the prince of physicians. However not much recent paper discussed on his practice on treating cancer. The review's goal was to discuss the background of Avicenna's bibliography and history in cancer study. This review encompasses 25 literatures and begins with a description of his profile and attitude. It then explains his medical background and interests, with an emphasis on cancer research. His contribution and a major milestone in cancer research were described. It also explains in great depth his perspective on cancer research. His proposed and implemented cancer prevention and treatment are listed and advised in order to lessen the negative impacts of cancer. To conclude, early detection and preventative measures aid in the reduction of cancer progression. In addition, plant base and less irritant treatment as well as improving the diet help to reduce malignancy. This review might contribute to give an insight to improve the current cancer treatment by looking back into the perspective of great scholar in medical field.